Історія хірургії пухлин коркового шару надниркових залоз (частина 1) - Рибаков, С. Й. (Clinical Endocrinology and Endocrine Surgery, 2013)
The lecture describes the history of the surgical technique development in the treatment of tumors of the adrenal cortex.